Natural resources in Argentina, Chile and Peru - Yang, Kian Seck (2011)
Argentina, Chile and Peru are among the South American countries blessed with an abundance of natural resources. The natural resource sectors, which include mining, oil and gas, agriculture, fisheries and forestry, have been the engine of economic growth in many ways. In order to promote the development in these sectors, particularly mining and oil and gas, the Governments of Argentina, Chile and Peru have embarked on a programme of deregulation to de-monopolise state-owned enterprises. Numerous policies have been introduced, incorporating various concessions, to attract foreign direct investment in the natural resource sectors. Many multinational companies have taken advantage of theses incentives and invested in activities such as exploration and extraction of minerals as well as manufacturing and food processing.